Istorijos būtis ir supančioji istorija: hermeneutinis žvilgsnis - Dubnikas, Kęstutis (Lietuvos istorijos studijos, 1997)
The contemporary philosophy of historiography widely discusses a problem of the cognitive claims. The article, following H. G. Gadamer’s hermeneutical philosophy and D. Tracy’s theory of "classics," dwells on an elaboration of the methodological distinction between, firstly, historical knowledge and secondly, an understanding of history. Historicism argues that history must be intelligible in the sense that it is so made by historians. From the hermeneutical point of view, conversely, the individual self-consciousness cannot be constituted neither along the lines of Cartesian Ego, nor along the lines of the Enlightenment’s understanding of a totally autonomous Ego. The historian is necessarily a historical being himself; he/she is deeply rooted in a concrete historical context. Both the historical consciousness and reality are mutually correlated. Historical facts, events or "classics" carry a complex plexus of life experiences and, thus, acquire a certain permanence of meaning which, in turn, could be itself interpreted as a result of analogical imagination.